2019
DOI: 10.4252/wjsc.v11.i10.748
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing survival, engraftment, and osteogenic potential of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are promising candidates for bone regeneration therapies due to their plasticity and easiness of sourcing. MSC-based treatments are generally considered a safe procedure, however, the long-term results obtained up to now are far from satisfactory. The main causes of these therapeutic limitations are inefficient homing, engraftment, and osteogenic differentiation. Many studies have proposed modifications to improve MSC engraftment and osteogenic differentiation of the transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 155 publications
0
40
0
Order By: Relevance
“…This low oxygen tension is also seen locally after musculoskeletal trauma and fracture, and in other instances of inflammation. Hypoxic conditions locally are important determinants of the subsequent function of osteogenic and vasculogenic progenitor cells (Volkmer et al, 2010 ; Garcia-Sanchez et al, 2019 ). The cellular response to hypoxia is generally controlled by the transcription factor hypoxia-inducible factor (HIF)-1.…”
Section: Methods To Enhance the Function Of Harvested Cells ( mentioning
confidence: 99%
“…This low oxygen tension is also seen locally after musculoskeletal trauma and fracture, and in other instances of inflammation. Hypoxic conditions locally are important determinants of the subsequent function of osteogenic and vasculogenic progenitor cells (Volkmer et al, 2010 ; Garcia-Sanchez et al, 2019 ). The cellular response to hypoxia is generally controlled by the transcription factor hypoxia-inducible factor (HIF)-1.…”
Section: Methods To Enhance the Function Of Harvested Cells ( mentioning
confidence: 99%
“…Customized scaffolds, made rapidly and efficiently by 3D printers, could easily reproduce the perfect shape for the lesion and correctly create the ideal niche for MSCs engraftment [ 40 ], and their osteogenic differentiation would be optimized by the oligostilbenes Res and Pol.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term engraftment of MSCs in vivo has proven to be challenging and has yet to be demonstrated, indicating MSCs may indirectly affect tendon healing. 99,100 Indeed, a role for MSCs as a cellular source of signals that promote healing of the endogenous tissue has been underscored by a recent effort to rename the cells as medicinal signaling cells. 101 As an alternative to adult stem cell-based cell therapies, studies in the last decade have shown the promise of directed stem cell differentiation approaches for cell replacement therapies to treat a variety of diseases and conditions.…”
Section: Emerging Cell-based Treatments and Engineering Strategiesmentioning
confidence: 99%